2021
DOI: 10.1038/s41438-021-00525-y
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the CmJAZ1-like gene delays flowering in Chrysanthemum morifolium

Abstract: Chrysanthemum (Chrysanthemum morifolium) is one of the four major cut-flower plants worldwide and possesses both high ornamental value and cultural connotation. As most chrysanthemum varieties flower in autumn, it is costly to achieve annual production. JAZ genes in the TIFY family are core components of the jasmonic acid (JA) signaling pathway; in addition to playing a pivotal role in plant responses to defense, they are also widely implicated in regulating plant development processes. Here, we characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…The most popular gene/protein families with direct or indirect influence on sex determination or with differential expression among sexes or those regulating hormones linked to sex ratio bias in other plant species are listed below. These are: Zinc finger, RING/FYVE/PHD-type [ 46 ]; Glycosyltransferase AER61 [ 47 ]; NAD(P)H-quinone oxidoreductase subunit L [ 48 ]; GLABROUS1 enhancer-binding protein [ 49 ]; Auxin efflux carrier [ 50 ]; Ribosomal protein PSRP-3/Ycf65 [ 15 ]; MADS-box [ 51 , 52 , 53 ]; Myb/SANT-like domain [ 54 ]; Aldolase-type TIM barrel [ 55 ]; NAD(P)-binding domain [ 56 ]; Zinc finger, Rad18-type putative [ 57 ]; Tify [ 50 , 58 ]; ABC transporter-like [ 59 , 60 ]; Homeodomain-like [ 61 , 62 ]; Prohibitin [ 63 ]; Initiation factor eIF-4 gamma, MA3 [ 64 ]; and HD-ZIP protein, N-terminal [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most popular gene/protein families with direct or indirect influence on sex determination or with differential expression among sexes or those regulating hormones linked to sex ratio bias in other plant species are listed below. These are: Zinc finger, RING/FYVE/PHD-type [ 46 ]; Glycosyltransferase AER61 [ 47 ]; NAD(P)H-quinone oxidoreductase subunit L [ 48 ]; GLABROUS1 enhancer-binding protein [ 49 ]; Auxin efflux carrier [ 50 ]; Ribosomal protein PSRP-3/Ycf65 [ 15 ]; MADS-box [ 51 , 52 , 53 ]; Myb/SANT-like domain [ 54 ]; Aldolase-type TIM barrel [ 55 ]; NAD(P)-binding domain [ 56 ]; Zinc finger, Rad18-type putative [ 57 ]; Tify [ 50 , 58 ]; ABC transporter-like [ 59 , 60 ]; Homeodomain-like [ 61 , 62 ]; Prohibitin [ 63 ]; Initiation factor eIF-4 gamma, MA3 [ 64 ]; and HD-ZIP protein, N-terminal [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jasmonic acid signals are generally modulated by biotic and abiotic stresses in crops, but studies have shown that excessive JAZ2 can promote tomato leaf growth and early flowering [ 56 ]. In chrysanthemums, excessive JAZ1-like levels cause bud formation and late flower development to occur at a significantly later time in transgenic plants than in the wild type [ 57 ]. This shows that the same hormone pathway may be affected by crosstalk between the regulation of the crop response to stress and the regulation of crop growth and development, resulting in the same type of genes performing multiple functions in crops.…”
Section: Discussionmentioning
confidence: 99%
“…Several TFs such as AP2/ERF , MYB , bHLH , MADS-box , and NAC have been previously characterized for their active role in development and flower initiation in plants. Our study identified TFs such as AP2/ERF [ 84 ], bHLH [ 85 ], FAR1 [ 86 ], mTERF [ 87 ], MYB-related [ 88 ], NAC [ 89 ], Tify [ 90 ], and WRKY [ 91 ] as major regulators involved in floral differentiation in E. japonicum . Ethylene-Responsive Factor ( ERF ) gene family is known for its diverse role in plant developmental process, including germination, flowering, maturation, and senescence [ 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%